Modelling an RDF Knowledge Graph with Transitivity and Symmetry for Bus Route Path Finding - Rathachai Chawuthai; Natthawut Kertkeidkachorn; Teeradaj Racharak (My University, 2023)
A key property of Linked Data is the representation and publication of data as an inter-connected labelled graph where different resources linked to each other form a network of meaningful information. A problem of path finding can be seen as searching important relationships between resources, such as, looking for chains of intermediate nodes. In this paper, we tackle this problem in the context of public transport navigation system, where we aim to find candidates of bus route path given two bus stations. We model a novel lightweight bus network as Resource Description Framework (RDF) triples of directed bus lines and walking paths between connected stations. Indeed, we demonstrate that lightweight bus network can be achieved by exploiting the sub-property of RDF Schema (RDFS) and the transitivity and symmetry provided by Web Ontology Language (OWL). We also perform a scalability test of our approach using a real-world bus network in Bangkok, Thailand. Various patterns of SPARQL Protocol and RDF Query Language (SPARQL) query statements are validated, showing the usefulness of the RDF model. The further step of this paper is to work with bus schedules and travel time analysis in order to select some proper candidates for users through an application.
Keywords: RDF Schema; Named graph; Linked Data; RDF query language; Semantic Web and Ontologies